2010
DOI: 10.1080/1091367x.2010.520244
|View full text |Cite
|
Sign up to set email alerts
|

Predicting VO2maxin College-Aged Participants Using Cycle Ergometry and Perceived Functional Ability

Abstract: The purpose of this study was to develop a multiple linear regression model to predict treadmill VO 2max scores using both exercise and non-exercise data. One hundred five college-aged participants (53 male, 52 female) successfully completed a submaximal cycle ergometer test and a maximal graded exercise test on a motorized treadmill. The submaximal cycle protocol required participants to achieve a steady-state heart rate equal to at least 70% of age-predicted maximum heart rate (220-age), while the maximal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Although age is generally inversely related to CRF, because this study involved a relatively homogenous sample of college students (18-29 years of age), age was not statistically significant in the prediction of CRF. Consistent with other research Nielson, et al, 2010) the results of this study found gender to be a significant predictor of CRF. The male participants (52.1 ± 6.5 mLkg -1 min -1 ) in this study had average VO 2 max values that were 19.5% greater than that of their female (43.6 ± 6.4 mLkg -1 min -1 ) counterparts.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although age is generally inversely related to CRF, because this study involved a relatively homogenous sample of college students (18-29 years of age), age was not statistically significant in the prediction of CRF. Consistent with other research Nielson, et al, 2010) the results of this study found gender to be a significant predictor of CRF. The male participants (52.1 ± 6.5 mLkg -1 min -1 ) in this study had average VO 2 max values that were 19.5% greater than that of their female (43.6 ± 6.4 mLkg -1 min -1 ) counterparts.…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between self-reported physical activity and CRF has previously been reported (Siconolfi, Lasater, Snow & Carleton, 1985) and regression models that include only non-exercise data (e.g., age, gender, body weight, body mass index, and self-reported physical activity) appeared in the 1990's Ainsworth, Richardson, Jacobs, & Leon,1992;Heil, Freedson, Ahlquist, Price, & Rippe, 1995;. More recent studies have combined exercise data and non-exercise data to predict CRF Nielson, George, Vehrs, Hager, & Webb, 2010). No other studies have combined exercise test data and self-reported physical activity or fitness levels to predict CRF from a step test.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This requires minimal space and is easy to transport. Cycle ergometer exercise is a no weight-bearing activity that is usually well tolerated by individuals with orthopedic or other physical limitations and the heart rate (HR), blood pressure, and electrocardiographic data are also easily collected during the test protocol [17].…”
Section: International Journal Of Diabetes and Metabolic Disordersmentioning
confidence: 99%
“…Nielson et al 32 built a MLR model for predicting treadmill VO 2 max scores using both exercise and nonexercise variables. For the study, 105 college-aged participants (53 males and 52 females) successfully accomplished a submaximal cycle ergometer test and a maximal GXT on a motorized treadmill.…”
Section: Hybrid Modelsmentioning
confidence: 99%